THE REQUIREMENT OF HOKKIEN LANGUAGE IN THE FIELD OF WORK - Indra Hartoyo (BAHAS, 2008)
This study was aimed to find out the requirement of Hokkien language in the field of work in Medan at present. The data were from three sources: job advertisements advertised in Analisa daily newspaper in January and March 2004, interviews to Tionghoa people and questionnaires sent to companies by their PO BOX number.  The results showed that there were 242 positions requiring Hokkien language offered in the two months. They were categorized into 14 types. Out of all the positions, Marketing/Sales seized the biggest portion, with the total number 90 or 37.19%. The second position was Bookkeeping & Accounting reaching 44 positions or 18.18%, and the third top was Administration, 24 positions or 9.92%. The three positions, in fact, were typical jobs of the Tionghoa. However, Education had also become an interesting business for them, as it took the fourth position. The reasons for requiring the language, according to two informants, were first because it was the language of social relations which might help with business relation, and second because business in Medan was dominated by the Tionghoa. The two reasons were actually to show their intimacy or closeness. Despite the fact that such requirement could cause discrimination, companies or business people did not want to take a chance for hiring those who were unable to speak the language. Both informants agreed that the language would only be useful in Medan but for international business affairs they suggested Mandarin Language. No results were found from questionnaires as no companies sent them back.